Effects of Early vs. Late Time-Restricted Eating on Cardiometabolic Health, Inflammation, and Sleep in Overweight and Obese Women: A Study Protocol for the ChronoFast Trial - Peters, Beeke; Koppold-Liebscher, Daniela A.; Schuppelius, Bettina; Steckhan, Nico; Pfeiffer, Andreas F. H.; Kramer, Achim; Michalsen, Andreas; Pivovarova-Ramich, Olga (Frontiers in Nutrition, 2021)
Background: Time-restricted eating is a promising dietary strategy for weight loss, glucose and lipid metabolism improvements and overall wellbeing. However, human studies demonstrated contradictory results for the restriction of food intake to the beginning (early TRE, eTRE) or to the end of the day (late TRE, lTRE) suggesting that more carefully controlled studies are needed. Objective: The aim of the ChronoFast trial study is to determine whether eTRE or lTRE is better dietary approach to improve cardiometabolic health upon minimized calorie deficits and nearly stable body weight. Methods: Here, we present the study protocol of the randomized cross-over ChronoFast clinical trial comparing effects of 2-weeks eTRE (8:00 to 16:00 hr) and lTRE (13:00 to 21:00 hr) on insulin sensitivity and other glycemic traits, blood lipids, inflammation and sleep quality in 30 overweight and obese women with increased risk of type 2 diabetes. To ensure timely compliance, unchanged dietary composition and to minimize possible calorie deficits, a real-time monitoring of dietary intake and body weight by smartphone app and extensive nutritional counselling will be used. Continuous glucose monitoring, oral glucose tolerance test, 24h activity tracking, questionnaires, and gene expression analysis in adipose tissue and blood monocytes will be used for assessment of study outcomes. Discussion: The trial will determine whether eTRE or lTRE is more effective to improve cardiometabolic health, elucidate underlying mechanisms, and contribute to the development of recommendations for medical practice and the wider population. Clinical Trial Registration: ClinicalTrials.gov; Identifier NCT04351672